Sandinistas : a moral history - Sierakowski, Robert J., 1983- (University of Notre Dame Press, 2019)
"Robert J. Sierakowski's Sandinistas: A Moral History offers a bold new perspective on the liberation movement that brought the Sandinista National Liberation Front to power in Nicaragua in 1979, overthrowing the longest-running dictatorship in Latin America. Unique sources, from trial transcripts to archival collections and oral histories, offer a new vantage point beyond geopolitics and ideologies to understand the central role that was played by everyday Nicaraguans. Focusing on the country's rural north, Sierakowski explores how a diverse coalition of labor unionists, student activists, housewives, and peasants inspired by Catholic liberation theology came to successfully challenge the legitimacy of the Somoza dictatorship and its entrenched networks of power. Mobilizing communities against the ubiquitous cantinas, gambling halls, and brothels, grassroots organizers exposed the regime's complicity in promoting social ills, disorder, and quotidian violence while helping to construct radical new visions of moral uplift and social renewal. Sierakowski similarly recasts our understanding of the Nicaraguan National Guard, grounding his study of the Somozas' army in the social and cultural world of the ordinary soldiers who enlisted and fought in defense of the dictatorship. As the military responded to growing opposition with heightened state terror and human rights violations, repression culminated in widespread civilian massacres, stories that are unearthed for the first time in this work. These atrocities further exposed the regime's moral breakdown in the eyes of the public, pushing thousands of previously unaligned Nicaraguans into the ranks of the guerrilla insurgency by the late 1970s. Sierakowski's innovative reinterpretation of the Sandinista Revolution will be of interest to students, scholars, and activists concerned with Latin American social movements, the Cold War, and human rights."--